Pengendalian Kualitas Benang Plastik Dengan Pendekatan Metode Statistical Process Control : Studi Kasus : PK. Rosella Baru - Mohammad Ilham; I Nyoman Lokajaya (Jurnal Kendali Teknik dan Sains, 2023)
PK. Rosella Baru is a company operating in the plastic sack industry. In the production process of plastic sacks, there are several stages, including the production of plastic thread. The company still encounters a significant number of defects in the plastic thread, exceeding 2%, resulting in obstacles in the weaving process of the sacks and suboptimal production output. The research utilizes the Statistical Process Control method to identify solutions for quality control of the plastic thread products at PK. Rosella Baru. Based on the Pareto diagram, the most dominant defect is found in the unevenness of thread rolls, accounting for 43.3% of the defects. The control chart analysis shows that there are samples exceeding the upper control limit (UCL) in samples 1 and 9, and data exceeding the lower control limit (LCL) in samples 3 and 6. The cause and effect diagram identifies five factors: labor, machine, material, method, and environment. The most dominant cause is the lack of training for the workforce and insufficient maintenance of the machines, resulting in defective plastic thread. Therefore, the suggested solution is to perform regular machine maintenance, provide training to the workforce, and pay attention to machine settings and the quality of raw materials used.